PENGARUH FINANCIAL STABILITY, FINANCIAL TARGET , NATURE OF INDUSTRY TERHADAP KECURANGAN LAPORAN KEUANGAN - Miftahul Falah; Aris Sanulika (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
. This study aims to examine and obtain empirical evidence on the effect of financial stability, financial target, and nature of industry on fraudulent financial reporting in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This research employs a quantitative approach using secondary data obtained from the Indonesia Stock Exchange (IDX) and the official websites of the respective companies. The analytical technique used in this study is panel data regression, processed using EViews version 10 software. The research sample consists of healthcare sector companies selected through purposive sampling, resulting in 100 observations from 20 companies over a five-year period (2020–2024). The results of this study indicate that, partially, financial stability and financial target have no effect on fraudulent financial reporting, while nature of industry partially has a effect on fraudulent financial reporting. Keywords: Fraudulent Financial Reporting, Financial Stability, Financial Target, Nature of Industry